An Evaluation of Lexical Density in K13 English Textbooks: Aligning Text Complexity with Students' Proficiency Levels - Sembiring, Pemina; Simanjuntak, Ivan Fernando; Sinar, Tengku Silvana (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study evaluates the lexical density of reading materials in the K13 English textbooks used in Indonesian secondary schools, focusing on the alignment of text complexity with students' cognitive abilities and language proficiency levels. A total of 10 reading texts from both junior and senior high school textbooks were analyzed, covering various genres including narrative, descriptive, expository, and functional texts. Lexical density, defined as the proportion of content words (nouns, verbs, adjectives, and adverbs) relative to the total word count, was calculated for each text. The results revealed significant variations in lexical density across genres, with descriptive and report texts exhibiting higher complexity, while genres like narratives and procedures showed a more balanced lexical composition. The study found that texts with higher lexical density may be challenging for lower-level learners, while more balanced texts are likely more accessible. These findings suggest that, while some texts are appropriately challenging, others may require adjustments to better cater to students' proficiency levels. The study highlights the importance of revising the K13 English textbooks to enhance their suitability for diverse learners and align more effectively with the goals of the K13 curriculum. The use of lexical density as an objective metric provides valuable insights for improving the readability and overall effectiveness of English language education in Indonesia. This research implies that curriculum designers and textbook authors should consider incorporating a wider range of text complexities to accommodate varying student proficiency levels, ensuring equitable learning opportunities and improved language development outcomes